Fibromyalgia Syndrome in a sample of Iraqi patients with psoriasis - Al-Bidri, Khudir Z.; Salman, Husam Ali; Al-Hassan, Yousra; Hasan, Mohammed Sahib (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Fibromyalgia syndrome and psoriasis share various soft problems. In addition, patients with psoriasis can experience subjective joint swelling and pain (Fibromyalgia syndrome) and objective swelling (Psoriatic arthritis) with the latter requiring systemic disease modifying antirheumatic drugs while the former requires anti-fibromyalgia measures. Objective: To assess the rate of fibromyalgia syndrome in a sample of Iraqi patients with psoriasis. Patients and Method: A sample of one hundred and twenty Iraqi patients with psoriasis and another one hundred and twenty healthy individuals matched for age and sex, serving as control group were studied. Full history was taken and complete clinical examination was done and various laboratory investigations were carried out for all individuals in both groups. The American College of Rheumatology 1990 criteria for Fibromyalgia syndrome were applied for individuals of both groups. Results: Fibromyalgia was present in 32 (26.7%) psoriatic patients compared to 13 (10.8%) individuals of the control group (P=0.0016). We found that psoriatic arthritis as well as treatment with systemic therapy (chemotherapy) are significant predictors for development of Fibromyalgia in a rate of 17 (14.2%) (p. value =0.001), 20 (16.7%) (p. value =0.0001) respectively. Conclusion: There is a significant association between Fibromyalgia Syndrome and psoriasis.